English Language Use in English Classrooms in Dutch Secondary Education Schools - Johanes Leonardi Taloko (Widya Mandala Surabaya Catholic University, 2008)
The Netherlands, like other European Union (EU) countries, concern about their education. They have been trying so hard to improve the quality of their education in all levels. In order to prepare their secondary school level students for internationalization among other EU members, they are interested in investigating what actually happens during the English lessons in all secondary school levels. By knowing all things they need to know, it is hoped that they can increase the quality of English lessons in those schools as well as the quality of student exchange program both inside and outside the country land. This study reports how much time Dutch teachers and students use English language during English lessons in VWO and VMBO.